Find the best answers to your questions at Westonci.ca, where experts and enthusiasts provide accurate, reliable information. Experience the convenience of finding accurate answers to your questions from knowledgeable experts on our platform. Discover in-depth answers to your questions from a wide network of professionals on our user-friendly Q&A platform.

Solve the following quadratic equation for all values of [tex]\( x \)[/tex] in simplest form:

\[ 4(x+2)^2 + 13 = 29 \ ]


Sagot :

Sure, let's solve the given quadratic equation step by step:

The original equation is:
[tex]\[ 4(x + 2)^2 + 13 = 29 \][/tex]

Step 1: Simplify the equation by isolating the quadratic term.
First, subtract 13 from both sides of the equation to remove the constant term on the left-hand side.
[tex]\[ 4(x + 2)^2 + 13 - 13 = 29 - 13 \][/tex]
[tex]\[ 4(x + 2)^2 = 16 \][/tex]

Step 2: Simplify the coefficient of the quadratic term.
Next, divide both sides of the equation by 4 to further isolate [tex]\((x + 2)^2\)[/tex].
[tex]\[ \frac{4(x + 2)^2}{4} = \frac{16}{4} \][/tex]
[tex]\[ (x + 2)^2 = 4 \][/tex]

Step 3: Solve for [tex]\(x + 2\)[/tex].
Take the square root of both sides of the equation to eliminate the square. Remember to consider both the positive and negative square roots.
[tex]\[ x + 2 = \pm\sqrt{4} \][/tex]
[tex]\[ x + 2 = \pm2 \][/tex]

Step 4: Solve for [tex]\(x\)[/tex].
Lastly, solve for [tex]\(x\)[/tex] by subtracting 2 from both sides in each case.
1. For [tex]\(x + 2 = 2\)[/tex]:
[tex]\[ x + 2 = 2 \][/tex]
[tex]\[ x = 2 - 2 \][/tex]
[tex]\[ x = 0 \][/tex]

2. For [tex]\(x + 2 = -2\)[/tex]:
[tex]\[ x + 2 = -2 \][/tex]
[tex]\[ x = -2 - 2 \][/tex]
[tex]\[ x = -4 \][/tex]

Summary:
The values of [tex]\(x\)[/tex] that satisfy the equation [tex]\(4(x + 2)^2 + 13 = 29\)[/tex] are:
[tex]\[ x = 0 \quad \text{and} \quad x = -4 \][/tex]

So, the solutions to the equation are:
[tex]\[ \boxed{0 \text{ and } -4} \][/tex]